Pengaruh Terapi Okupasi pada Pasien Skizofrenia dengan Defisit Perawatan Diri di Ruang Intensif: Case Report - Auladia Muftikha; Laili Nur Hidayati; Akrim Wasniyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The most serious and chronic mental disorder is schizophrenia. Schizophrenia sufferers often have limitations that greatly affect the performance of daily activities, one of which is carrying out self-care. Increasing independence from self-care deficit problems can be overcome with non-pharmacological management, one of which is occupational therapy. Occupational therapy intervenes in limitations by seeking greater autonomy of the patient through certain activities. The aim of the case study is to determine the effect of occupational therapy on the patient's level of independence in the intensive care unit. The method used is a case study with a nursing care approach. A case study was conducted at a mental hospital in 2024 involving a 56 year old patient. The instrument used was the Activity of Daily Living questionnaire. Occupational therapy was carried out for 12 days. The results of the study showed that there was an increase in the level of independence in carrying out self-care from a score of 10 to 17 and a decrease in signs of self-care deficit symptoms in patients from 9 to 2. Based on the results, it can be concluded that occupational therapy can increase the level of independence and reduce signs of deficit symptoms patient self-care.